2021
DOI: 10.3390/molecules26113236
|View full text |Cite
|
Sign up to set email alerts
|

Spent Grain from Malt Whisky: Assessment of the Phenolic Compounds

Abstract: In order to extract antioxidant phenolic compounds from spent grain (SG) two extraction methods were studied: the ultrasound-assisted method (US) and the Ultra-Turrax method (high stirring rate) (UT). Liquid to solid ratios, solvent concentration, time, and temperature/stirring rate were optimized. Spent grain extracts were analyzed for their total phenol content (TPC) (0.62 to 1.76 mg GAE/g SG DW for Ultra-Turrax pretreatment, and 0.57 to 2.11 mg GAE/g SG DW for ultrasound-assisted pretreatment), total flavon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
(79 reference statements)
1
9
0
Order By: Relevance
“…Chemical composition of spelt flour was (%w/w, dry basis): 3 ± 0.01% lipids, 8 ± 0.05% fiber, 14 ± 0.09% protein, 64 ± 1.15% carbohydrates, 2.11 ± 0.04% ash, 11.26 ± 0.08% moisture, 313 ± 1.14 s falling number, 32.73 ± 2.14% wet gluten, 2 ± 0.02 mm gluten deformation index, and 74 ± 1.54% hydration capacity. Spent grain flour had the following characteristics (%w/w, dry basis): moisture (5.04 ± 0.42%), ash (3.47 ± 0.02%), protein (18.88 ± 0.37%), lipids (7.11 ± 0.39%), and fibers (22.67 ± 0.42%), as we obtained from previous study [20]. The addition of spent grain in pasta formulation was analyzed on rheological properties of dough, and on dry and cooked pasta.…”
Section: Resultssupporting
confidence: 62%
“…Chemical composition of spelt flour was (%w/w, dry basis): 3 ± 0.01% lipids, 8 ± 0.05% fiber, 14 ± 0.09% protein, 64 ± 1.15% carbohydrates, 2.11 ± 0.04% ash, 11.26 ± 0.08% moisture, 313 ± 1.14 s falling number, 32.73 ± 2.14% wet gluten, 2 ± 0.02 mm gluten deformation index, and 74 ± 1.54% hydration capacity. Spent grain flour had the following characteristics (%w/w, dry basis): moisture (5.04 ± 0.42%), ash (3.47 ± 0.02%), protein (18.88 ± 0.37%), lipids (7.11 ± 0.39%), and fibers (22.67 ± 0.42%), as we obtained from previous study [20]. The addition of spent grain in pasta formulation was analyzed on rheological properties of dough, and on dry and cooked pasta.…”
Section: Resultssupporting
confidence: 62%
“…The linear and quadratic models that were fitted on each response were evaluated. The chemical composition of spelt flour is described in Table 1, which we obtained from a previous study [39]. The mathematical models were significant and presented the responses accurately; in all cases, the F-value was significant (p < 0.01), and R 2 values were more than 0.87, according to the ANOVA results presented in Table 2.…”
Section: Model Fitting and Statistical Analysismentioning
confidence: 68%
“…Moreover, Zhang et al (2015) reported that DPPH was correlated to TPC during ultrasonic treatment. In contrast, Chetrariu and Dabija (2021) reported that an ultrasound-assisted method could increase the DPPH of the samples. It was also reported that DPPH has a positive trend with the duration of alcoholic beverage maturation (Fraser & Francis, 2021).…”
Section: Dpph Assay Scavenging Activitymentioning
confidence: 94%
“…The samples' DPPH scavenging activity was measured following a previously published work (Chetrariu & Dabija, 2021). The 2 ml sample was mixed with 2 m of DPPH (SIGMA‐ALDRICH, Co, USA) and 0.1 mM in methanol (Fine Chemicals, USA).…”
Section: Methodsmentioning
confidence: 99%